The Dynamics of State Administrative Law and the Role of Government in Upholding Social Justice: A Case Study of Public Policy Management in the Era of Digital Technology - Galluci, Angga (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The increasing adoption of digital technology in public administration processes has brought about fundamental changes in the implementation and understanding of administrative law. The presence of technology not only influences patterns of government interaction with the public but also presents new challenges in the application of legal principles such as transparency, accountability, and public participation. Previous research has shown that digitalization can increase the efficiency and effectiveness of public services, but on the other hand, it also raises serious problems, including the risk of corruption in public policymaking and the digital divide. This research aims to analyze the dynamics of state administrative law and the role of government in upholding social justice in the digital era. The main focus of the study is on the alignment of administrative law with technological developments, particularly in the management of digital-based public policies. The research method used is normative legal research, using approaches from legislation, doctrine, and related legal literature. The results show that the government's role in the digital era is not limited to providing public services, but also as a regulator, facilitator, and innovator. Regulations such as Law No. 1 of 2024 concerning Electronic Information and Transactions (ITE), Law No. 25 of 2009 concerning Public Services, and Regulation of the Minister of Administrative and Bureaucratic Reform No. Law No. 11 of 2024 is a crucial foundation for ensuring social justice in the digital realm. However, challenges remain, including personal data protection, potential algorithmic bias, and limited public digital literacy. Therefore, this study concludes that the alignment of state administrative law with digital transformation is a key prerequisite for creating transparent, accountable, participatory, and inclusive governance. Strengthening regulations, increasing the digital literacy of civil servants, and increasing public participation are key strategies for realizing social justice in the digital era.